2016
DOI: 10.1002/anie.201605838
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Stabilized Borylenes and Boryl Anions as Ligands? Redox Reactivity in Boron‐Based Pincer Complexes

Abstract: Stabilized borylenes (L BH:) with weakly π-accepting substituents L, such as phosphines, were previously believed to be unstable. In the current manuscript, we describe a series of complexes formally containing a phosphine-stabilized borylene or boryl anion. In contrast to common trivalent boron compounds, the boron-based ligands in this study act as electron-donating ligands. The reported iron hydride complexes exhibit a unique reactivity pattern, undergoing a reversible B-H reductive elimination concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 93 publications
6
57
0
2
Order By: Relevance
“…Several tricoordinated boron systems (borylene) are reported in the literature, where the boron centers are nucleophilic in nature . Such nucleophilic nature is confirmed by complexation with metal complexes . Ligands that have been used to stabilize these systems are strong σ‐donors and π‐acceptors, such as CAAC, CN, and CO. Other nucleophilic boron compounds are known, such as boroles, boryl anions, and diazadiborinines .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several tricoordinated boron systems (borylene) are reported in the literature, where the boron centers are nucleophilic in nature . Such nucleophilic nature is confirmed by complexation with metal complexes . Ligands that have been used to stabilize these systems are strong σ‐donors and π‐acceptors, such as CAAC, CN, and CO. Other nucleophilic boron compounds are known, such as boroles, boryl anions, and diazadiborinines .…”
Section: Methodsmentioning
confidence: 98%
“…This is yet another confirmation of higher nucleophilicity of the boron center induced by PH 3 . The recent realization of bis‐phosphine stabilized borylene system (Figure S8 in the Supporting Information) strongly suggests that 3 c would be a promising target for synthetic efforts …”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we reported the formation of PBP‐type pincer complexes through dehydrogenative P−B bond formation of phosphine‐borane complexes . In continuation of this work, we investigated the reactivity of other metal precursors in these P−B bond‐forming reactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the metal oxidation state and the nature of the ancillary ligands, the substituents at the boron atom seem to be essential for the observed reactivity patterns. For N‐ and C‐based substituents at boron, hydride‐transfer and dihydrogen elimination are observed between the metal and the ligand,,, whereas for phosphine substituents, a pronounced redox reactivity between the metal and boron atom takes place …”
Section: Introductionmentioning
confidence: 99%
“…However, the further degradation of boryl intermediates such as C to complexes with a boron‐based donor ligand ( D ) has not been considered to be a viable mechanistic scenario so far. Recently, we reported the formation of an iron complex with such a phosphine‐stabilized borylene as ligand (type D ) and provided evidence for pathway A → D . Although the reactivity of transition metal boryl and borylene complexes has been discussed extensively, examples of base‐stabilized borylenes and their transition metal complexes are still rare .…”
Section: Introductionmentioning
confidence: 99%